Perceived motor competence in children from two different perspectives: children and family - Andrea Hernández-Martínez; Yolanda Sánchez-Matas; Verónica Arréala Fernández (Desafio Singular, 2022)
Perceived motor competence (PMC) is fundamental in early childhood because of its relationship with the development of motor competence (MC). Therefore, the aims of the present research were: to analyse children's PMC from their own and their parents' perspectives, to test for gender differences, and to assess the possible association between children's PMC and their parents' perception. The sample consisted of 22 children in the third year of kindergarten (M = 5.27, SD = 0.45) and their respective parents. The results showed higher scores for girls in the scales' patterns, except for object control. The girls also scored higher on all dimensions from parents, with significant differences in parents' perception of fine motor skills in their favour. No relevant data were found on the relationship between the children's PMC and parents´ perception. It can be concluded that girls' perception is higher than boys' and that girls are perceived as more competent by their parents. However, the lack of correspondence between children's and parents' perceptions makes it necessary to be cautious and consider that participants may not be accurate in their assessments due to their age.